Impacts of Tropical Cyclones on Longleaf Pine Ecosystems of Florida: Tropical Cyclogenesis, Landfall Frequencies, and Climate Change - Gilliam, Frank S. (Frontiers in Ecology and Evolution, 2021)
Tropical storms and hurricanes (collectively hereafter, tropical cyclones) are among the most destructive forces in nature. These threats are of particular concern to human populations and ecosystems of coastal areas of the southeastern United States, most especially in the State of Florida. This review begins with an overview of the effects of tropical cyclones on Florida’s most conspicuous terrestrial ecosystem—longleaf pine. Environmental factors leading to tropical cyclogenesis will also be reviewed, with a specific focus on (1) landfall history in Florida, and (2) the potential relationship between climate change and the frequency/intensity of tropical cyclones in the North Atlantic Ocean. Given its geographical distribution, it is not surprising that longleaf pine has long been impacted by tropical cyclones of the North Atlantic. Tropical cyclones are formed from a complex combination of meteorological conditions, driven initially by the release of excess heat from the surface waters of the ocean, along with an unstable atmosphere comprising air temperatures decreasing and wind speeds increasing with altitude. Among the coastal counties from Texas to Maine, those of Florida have experienced by far the highest frequency of tropical cyclones, especially the southern tip of peninsular Florida, with its most populous county (Miami-Dade) receiving 25 hits from 1900 to 2010, second only to Monroe County (32 hits) during that period. Frequencies of all categories of cyclones have increased significantly from 1850 to the present. Cyclone frequencies were significantly correlated with increases in air and ocean temperatures, both of which have increased over the past, suggesting a causal relationship with anthropogenic climate change. Of future concern is how increases in frequencies and intensities of tropical cyclones will negatively affect the structure and function of these ecologically and economically important longleaf pine ecosystems.